THE MATERIALIZATION OF IDENTITY: ARCHITECTURE AND CONSUMPTION IN THE LATE ROMAN VILLAS OF LUSITANIA - Noé CONEJO (Journal of Ancient History and Archaeology)
Like in the rest of Hispania, the rural world in Lusitania underwent significant changes during the late 3rd and 4thcenturies. During this period, numerous rural residences, characterized by great monumentality and complex decoration, were renovated or built. Like in the rest of the western Mediterranean, the emergence of these rural buildings is related to the new political, economic and social order that followed the tetrarchic period, which was characterized in Lusitania and Hispania by the designation of Augusta Emerita (Mérida, Badajoz) as the capital of the Diocese Hispaniarum and the renewal of aristocratic cadres, with the inclusion in the Senate Ordo of bureaucrats and the military. In this socio-political setting, marked by competition and social promotion, rural residences became true centres of social prestige, where architecture and conspicuous consumption were used as a language to display the economic power and the social status of the ownersto visitors and guests. The detailed analysis of the architecture and other markers of consumption documented in various villages in Lusitania will help to comprehendwhat messages the rural owners exactly wanted to convey, contributing to a greaterunderstanding of the social codes of this privileged group.